ANALISIS RESEPSI PENONTON TERHADAP DUKUNGAN BAGI KORBAN KEKERASAN SEKSUAL DALAM SERIAL UNBELIEVABLE - Nadifah, Roudotun (Universitas Negeri Surabaya, 2024)
Sexual violence can be happened anywhere, both in public and domestic spaces. It can also happen to anyone regardless of age, gender or social background. In this research, researcher focus on discussing the issue of sexual violence that occurs against women in the domestic space which is show in the form of the Netflix film series